Meta‐Analysis of Tumor Necrosis Factor Inhibitors and Glucocorticoids on Bone Density in Rheumatoid Arthritis and Ankylosing Spondylitis Trials. Issue 6 (May 2015) - Siu, Stephanie; Haraoui, Boulos; Bissonnette, Robert; Bessette, Louis; Roubille, Camille; Richer, Vincent; Starnino, Tara; McCourt, Collette; McFarlane, Alexandra; Fleming, Patrick; Kraft, John; Lynde, Charles; et al.
<x xml:space="preserve">Abstract</x> Objective To examine the impact of antirheumatic drugs on bone mineral density (BMD) in rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), and psoriasis using a systematic review. Methods Electronic databases were systematically searched for randomized controlled trials. Studies were grouped based on disease, treatment, and site of BMD measurement. Change in BMD (ΔBMD) from baseline to end of study was recorded. Standardized mean difference (SMD) of ΔBMD between treatment and controls was standardized for meta‐analyses and 95% confidence intervals (95% CIs) were calculated. Results Treatment effects on BMD were not the primary outcomes of the trials. Thirteen studies were eligible (11 RA, 2 AS, 0 PsA, and 0 psoriasis). For RA, significantly less hand bone loss was seen with tumor necrosis factor inhibitors (TNFi; SMD ΔBMD 0.33 [95% CI 0.13, 0.53], P = 0.001, I2 = 0%) and glucocorticoids (SMD ΔBMD 0.51 [95% CI 0.20, 0.81], P = 0.001, I2 = 0%). TNFi had no significant effect on lumbar spine and hip BMD. Glucocorticoids were associated with a negative effect on lumbar spine (SMD ΔBMD −0.30 [95% CI −0.55, −0.04], P = 0.02, I2 = 52%), but not hip BMD. For AS, a significant increase in BMD was seen with TNFi at the lumbar spine (SMD ΔBMD 0.96 [95% CI 0.64, 1.27], P < 0.001, I2 = 16%) and hip (SMD ΔBMD 0.38 [95% CI 0.13, 0.62], P = 0.003, I2 = 0%). Data were insufficient to perform meta‐analyses in PsA and psoriasis or for other antirheumatic drugs. Conclusion In RA, TNFi and glucocorticoids appeared to attenuate hand bone loss. TNFi did not impact lumbar spine and hip BMD and glucocorticoids had negative effects on lumbar spine and no effect on hip BMD. In AS, TNFi was associated with improved lumbar spine and hip BMD.